Pengaruh Variasi Pemanasan Awal Udara dan Penambahan Udara Bantu Pada Reaktor Terhadap Performa Kompor Gasifikasi Sekam Padi Top Lit Up Draft (TLUD) - Murdiono, Gilang; , Wijianto, ST., M.Eng.Sc (2017)
Abstact One of technology that using gasification is top lit up draft gasification stove.the objective of this study is to know the effect of variation inlet air heating and air addition on reactor toward perfomance of top lit up draft gasification stove. This study using top lit up draft gasification stove with 2 methods of test with air addition on reactor and test with no air addition on reactor every test have variation of begin air temperature and air velocity. Begin air temperature that use is 320C,500C,700C and every temperature test with 8 m/s,10m/s, 12m/s and then measuring combustion temperature, water temperature, and effectiveness burning. The result of this study shown high value of begin air temperature and with air addition on reactor then high value too the combustion temperature and short time effectiveness burning produces the result same when adding air on reactor, the best thermal efficiency get 500C begin air temperature with 10m/s air velocity thermal efficiency is about 15,958 %.